2013
DOI: 10.1371/journal.pone.0074126
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Interleukin-10 and Its Genetic Variations with Ischemic Stroke in a Chinese General Population

Abstract: Background and PurposeAnti-inflammatory cytokine and its genetic variations may play an important role in the process of atherosclerosis. We assessed whether serum interleukin-10 (IL-10) and its genetic variations are associated with ischemic stroke in a Chinese general population.MethodsAn epidemiological survey on cardiovascular diseases and their risk factors was carried in a general population in Beijing in 2005. Serum IL-10, IL-6, p-selectin, soluble intercellular adhesion molecule-1 and C-reactive protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 22 publications
1
30
1
3
Order By: Relevance
“…analysed the SNP rs1554286 of IL10 in 807 Indian patients and found a strong association between rs1554286 and leprosy . The SNP rs1554286 (TT vs. CT and CC genotype, OR = 1·59; 95% CI 1·06–2·39) was significantly associated with ischaemic stroke even after controlling for age, sex, smoking, systolic blood pressure, total cholesterol, glucose, body mass index and serum IL‐10 in a case–control study …”
Section: Discussionmentioning
confidence: 97%
“…analysed the SNP rs1554286 of IL10 in 807 Indian patients and found a strong association between rs1554286 and leprosy . The SNP rs1554286 (TT vs. CT and CC genotype, OR = 1·59; 95% CI 1·06–2·39) was significantly associated with ischaemic stroke even after controlling for age, sex, smoking, systolic blood pressure, total cholesterol, glucose, body mass index and serum IL‐10 in a case–control study …”
Section: Discussionmentioning
confidence: 97%
“…The authors of previous studies have reported an association between IL10 gene polymorphisms and the development of cerebrovascular diseases; however, the results are inconsistent (Balding et al, 2004;Trompet et al, 2007;Munshi et al, 2010;Sultana et al, 2011;Xie et al, 2013;Chao et al, 2014). Balding et al (2004) found that IL10 gene polymorphisms were not associated with ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Munshi et al (2010) conducted a study in Caucasians and revealed that individuals bearing A allele of IL10 -1082A/G gene were more predisposed to stroke. Xie et al (2013) reported that the individuals carring IL10 rs1800872 and rs3021094 gene variant exhibited a significantly association with risk of ischemic stroke in a Chinese population. A recent meta-analysis pooled 16 studies and revealed that the AA genotype of IL10 -1082A/G is associated with the risk of ischemic stroke (Chao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this, Pinderski Oslund et al found that activated T-lymphocytes overexpress the antiinflammatory cytokine interleukin-10 (IL-10), and that this event is capable of blocking AS actions in vitro and in vivo (57,58). Xie et al showed in a cross-sectional study that decreased serum IL-10 concentrations were significantly associated with an increased likelihood of ischemic stroke (59). Further, IL-10 expression was found elevated in advanced and unstable AS-plaques (60), and it appears to contribute to the regulation of the local inflammatory response, and is involved in the control of cell death within plaques (60)(61)(62)(63).…”
Section: Interleukin-10 -The Antiinflammatory "Master" Cytokinementioning
confidence: 99%